Reactive Oxygen Species and Nrf2: Functional and Transcriptional Regulators of Hematopoiesis. (18th November 2019) - Hu, Linping; Zhang, Yawen; Miao, Weimin; Cheng, Tao
Abstract : Hematopoietic stem cells (HSCs) are characterized by self-renewal and multilineage differentiation potentials. Although they play a central role in hematopoietic homeostasis and bone marrow (BM) transplantation, they are affected by multiple environmental factors in the BM. Here, we review the effects of reactive oxygen species (ROS) and Nrf2 on HSC function and BM transplantation. HSCs reside in the hypoxic microenvironment of BM, and ROS play an important role in HSPC regulation. Recently, an extraphysiologic oxygen shock/stress phenomenon was identified in human cord blood HSCs collected under ambient air conditions. Moreover, Nrf2 has been recently recognized as a master transcriptional factor that regulates multiple antioxidant enzymes. Since several years, the role of Nrf2 in hematopoiesis has been extensively studied, which has functional similarities of cellular oxygen sensor hypoxia-inducible factor-1 as transcriptional factors. Increasing evidence has revealed that abnormally elevated ROS production due to factors such as genetic defects, aging, and ionizing radiation unexceptionally resulted in lethal impairment of HSC function and hematopoiesis. Both experimental and clinical studies have identified elevated ROS levels as a major culprit of ineffective BM transplantation. Lastly, we discuss the possibility of using small molecule antioxidants, such as N-acetyl cysteine, resveratrol, and curcumin, to augment HSC function and improve the therapeutic efficacy of BM transplantation. Further research on the function of ROS levels and improving the efficacy of BM transplantation may have a great potential for broad clinical applications of HSCs.